PREVALENCE OF DEPRESSION AMONG SCHOOL GOING ADOLESCENTS IN BAREILLY DISTRICT (URBAN) - Raj Shekhar Tiwari; Shwetambari Tiwari (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Depression is one of the most common global mental health problems. In adolescents, it is one of the under-recognized health problems due to the inability to disclose their feelings and reluctance to seek psychiatric help. In the last century, the medical community did not accept the existence of depressive disorders in children. It was believed that children are lacking the mature psychological and cognitive structure needed to experience symptoms related to depressive disorders. Methods- This prospective cross-sectional survey was conducted on school going adolescents of public and private schools of Bareilly district during period of October 2016- November 2017. All the students of both genders of 10 to 18 years of age who were present on the day of visit were included in this study.The study tool used for detecting early symptoms of depression in adolescents was simple screening psychological instrument: Beck Depression Inventory (BDI). Results-This study has shown a significant level of depressive symptoms in a school sample of adolescents in a Bareilly city. Considering that 42.4% of 145 depressed adolescents in this study reported moderate to severe depression, it is understood that a considerable number of adolescents are experiencing turmoil during this phase. This could result in further problems like poor academic performance, poor coping methods and suicidal ideations.